1987
DOI: 10.1111/j.1476-5381.1987.tb11351.x
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of frog neuromuscular transmission by sodium fluoride

Abstract: 1 The effects of sodium fluoride (NaF, 5 mM) alone or in combination with theophylline (1.5 mM) or imidazole (1.5 mM) on the amplitude of the endplate potential (e.p.p.), frequency of the miniature endplate potential (m.e.p.p.), and the quantal content ofthe e.p.p. of bullfrog muscle were investigated.The effects of forskolin (I jM) and papaverine (1 pM) on the m.e.p.p. frequency were also studied.2 NaF caused an increase of 22% in the amplitude of the e.p.p. This NaF-induced increase was enhanced by theophyll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Evidence to support a role of cyclic AMP in this response was the finding that forskolin, cholera toxin and 8-bromo cyclic AMP each mimicked the effect of isoprenaline. These results are in complete agreement with the effect of cyclic AMP-elevating drugs on neuromuscular transmission (Breckenridge et al, 1967;Goldberg & Singer, 1969;Wilson, 1974;Standaert & Dretchen, 1979;Hattori & Maehashi, 1987;Wessler & Anschutz, 1988;Dryden et al, 1988;Wessler et al, 1990b) and suggest that cyclic AMP may be intimately involved in regulating the biosynthesis, storage and exocytosis of ACh (Wilson, 1974). It is not yet known how an increase in cyclic AMP levels could lead to facilitation of ACh release but it has been suggested that phosphorylation of proteins associated with synaptic vesicles increases the availability of the transmitter for exocytotic release (Dryden et al, 1988).…”
Section: Discussionsupporting
confidence: 74%
“…Evidence to support a role of cyclic AMP in this response was the finding that forskolin, cholera toxin and 8-bromo cyclic AMP each mimicked the effect of isoprenaline. These results are in complete agreement with the effect of cyclic AMP-elevating drugs on neuromuscular transmission (Breckenridge et al, 1967;Goldberg & Singer, 1969;Wilson, 1974;Standaert & Dretchen, 1979;Hattori & Maehashi, 1987;Wessler & Anschutz, 1988;Dryden et al, 1988;Wessler et al, 1990b) and suggest that cyclic AMP may be intimately involved in regulating the biosynthesis, storage and exocytosis of ACh (Wilson, 1974). It is not yet known how an increase in cyclic AMP levels could lead to facilitation of ACh release but it has been suggested that phosphorylation of proteins associated with synaptic vesicles increases the availability of the transmitter for exocytotic release (Dryden et al, 1988).…”
Section: Discussionsupporting
confidence: 74%
“…Experimental treatments designed to accelerate the activity of kmases increase transmitter release at frog neuromuscular junctions ( NMJs) (Publicover, 1983(Publicover, , 1985Eusebi, Molinaro, and Cardtsch, 1986;Haimann, Meldolesi, and Ceccarelli, 1987;Caratsch, Shumacher, Grassi, * To whom correspondence should be addressed. and Eusebi, 1988;Hattori and Maehashi, 1987;Shapira, Silberberg, Ginsburg, and Rahamimoff, 1987), crustacean NMJs (Dixon and Atwood, 1989;Gilat and Hochner, 1990), mammalian NMJs (Wilson, 1974;Ribeiro and Walker, 1975;Murphy and Smith, 1987;Dryden, Singh, Gordon, and Lazarenko, 1988), and in synapses of mammalian brain (Malenka, Madison, and Nicoll, 1986;Malenka, Ayoub, and Nicoll, 1987). However, the role played by phosphatases in regulating synaptic transmission has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In the double‐cocktail experiment, quantal release estimates were made for control, followed by application of the selective PDE inhibitor papaverine (10 µmol/L) and the selective adenosine receptor antagonist 8‐cyclopentyl‐1,3 dipropylxanthine (DPCPX; 0.1 µmol/L) in the absence and presence of theophylline. Papaverine was chosen because it has been demonstrated to enhance transmitter release and is a more selective PDE inhibitor 18 . Although 3 µmol/L papaverine is very effective in altering transmitter release, we used 10 µmol/L papaverine to ensure that PDE was maximally inhibited.…”
Section: Methodsmentioning
confidence: 99%
“…Papaverine was chosen because it has been demonstrated to enhance transmitter release and is a more selective PDE inhibitor. 18 Although 3 mmol / L papaverine is very effective in altering transmitter release, we used 10 mmol / L papaverine to ensure that PDE was maximally inhibited. This cocktail was used to effectively eradicate the antagonistic effect of theophylline on adenosine receptors and PDE, two of its three potential sites of action.…”
Section: Methodsmentioning
confidence: 99%